Antibacterial activity of novel peptides isolated from protein hydrolysates of RuBisCO purified from green juice alfalfa. (October 2015) - Kobbi, Sabrine; Balti, Rafik; Bougatef, Ali; Le Flem, Guillaume; Firdaous, Loubna; Bigan, Muriel; Chataigné, Gabrielle; Chaabouni, Semia; Dhulster, Pascal; Nedjar, Naima
Highlights: Antibacterial activity of protein hydrolysates of RuBisCO. Hydrolysate, with a DH of 18.8%, obtained by treatment with pepsin displayed the highest activity. Molecular mass and amino acid sequence of bioactive peptides were determined using ESI–MS and ESI–MS/MS. New pure antibacterial peptides (Met-Asp-Asn), (Asn-Arg-Asn-Ala-Cys) and (Leu-Arg-Asp-Asp-Phe) were identified. Abstract: The present paper reports on the isolation and characterization of novel bioactive peptides by the hydrolysis of RuBisCO proteins. Antibacterial activity was evaluated against Gram-negative ( Escherichia coli and Salmonella enterica ) and Gram-positive ( Listeria innocua, Staphylococcus aureus, Enterococcus faecalis, Micrococcus luteus and Bacillus subtilis ) bacteria. A simple method, consisting in the precipitation of the active peptides under ionic strength and pH conditions, was used to separate antimicrobial peptides from complex peptic hydrolysates of RuBisCO obtained by treatment with Pepsin ® (DH = 18.8%). The obtained peptide extract was fractionated using RP-HPLC, and the active fractions were analyzed by liquid chromatography, electrospray ionization, and tandem mass spectrometry (LC-ESI-MS). Among a total of twelve identified peptides, three new pure antibacterial peptides, namely(Met-Asp-Asn ), (Glu-Leu-Ala-Ala-Ala-Cys ) and (Leu-Arg-Asp-Asp-Phe ), were obtained under hydrolytic conditions. The latter peptides were highly active against the tested strains. The three peptides did not show hemolytic activity towards bovine erythrocytes. Taken together, the results suggest that the new peptides isolated from RuBisCO could offer potential ingredients for the functional foods industry.